Implementasi Konsep Akuntansi Syariah Dalam Pembangunan Infrastruktur Pada Ekonomi Biru Di Indonesia - Ardila Nasution; Kamilah Kamilah (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
There are 514 urban areas in the archipelagic nation of Indonesia (Ministry of Home Affairs, 2016). There are many cities in Indonesia that are able to provide a sense of comfort and security for their residents, this of course has an impact on population growth. However, the amount of waste that can be generated and stored is limited by the carrying capacity of the urban environment. Using the idea of ​​a "green city" which consists of nine elements of road infrastructure, traffic, green open space, clean water, noise, energy, housing, clean air and buildings is one way to overcome the above problems. All these qualities need to be utilized immediately with a comprehensive systems approach and in accordance with economic, social and environmental principles in sustainable development. Blue economy approaches can be used to eliminate waste. The “blue economy” is a term that is becoming increasingly popular in today's seas and oceans. The aim of this concept is to combine sea base development opportunities with environmental management and protection. Four conceptual interpretations of the blue economy were determined through research into the dominant discourse in international economic policy documents. How the blue economy works is also examined through an “in practice” analysis of the blue economy and related actors. Next, the scope and focus of the blue economy is explored specifically on the maritime industry, which is included or excluded in various conceptualizations. This analysis reveals areas of agreement and conflict. The consensus range reflects the growing trend towards the commercialization and valuation of nature, delineating and defining maritime boundaries and enhancing the security of the world's oceans. There are several areas of conflict, particularly disputes over the legitimacy of individuals as part of the “blue economy”, highly carbon-intensive industries such as oil and gas and the growing deep sea mining industry. Oceans are becoming increasingly important in terms of potential international trade opportunities through intermediaries and buyers. the behavior of the model supporting such a relationship in the ocean is acceptable from a regular and economic point of view. The relationship between land and sea is increasing in the role and importance of the "blue economy" as the term emerges in the background. . A literature review was conducted to analyze the correct definition of the blue economy. This definition is analyzed based on the minimum requirements that are important for the blue economy. This article also tries to compile various types of activities related to marine services. This is done to determine what can be considered priority areas for blue economic growth. The blue economy concept is based on national economic development. This is comprehensively useful for achieving overall national development. Environmental accounting is stated as a process of reducing negative values ​​and creating positive values ​​in environmental accountability.